Aspek Mental Siswa yang Mengikuti Kegiatan Latihan Pencak Silat Raksa Budhi di Kabupaten Karawang - Riki Yohanes; Rizki Aminudin; Rhama Nurwansyah (Universitas Singaperbangsa, 2021)
This study aims to determine how much the mental level of students who take part in the Raksa Budhi pencak silat training activity in Karawang Regency based on intrinsic and extrinsic factors. The subjects in this study were students who participated in the Raksa Budhi pencak silat training activity in Karawang Regency and had already competed in a championship. Data collection techniques carried out in this study using a questionnaire or questionnaire. The method used was a survey, while the data collection technique used a questionnaire, the questionnaire in this study was in the form of a Likert scale. The results of the study showed that the mental aspects of students who participated in the Raksa Budhi Pencak Silat training activity in Karawang regency in facing the competition stated that they were in the